6(2-x)-8x=8(x+7)

Simple and best practice solution for 6(2-x)-8x=8(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-x)-8x=8(x+7) equation:


Simplifying
6(2 + -1x) + -8x = 8(x + 7)
(2 * 6 + -1x * 6) + -8x = 8(x + 7)
(12 + -6x) + -8x = 8(x + 7)

Combine like terms: -6x + -8x = -14x
12 + -14x = 8(x + 7)

Reorder the terms:
12 + -14x = 8(7 + x)
12 + -14x = (7 * 8 + x * 8)
12 + -14x = (56 + 8x)

Solving
12 + -14x = 56 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
12 + -14x + -8x = 56 + 8x + -8x

Combine like terms: -14x + -8x = -22x
12 + -22x = 56 + 8x + -8x

Combine like terms: 8x + -8x = 0
12 + -22x = 56 + 0
12 + -22x = 56

Add '-12' to each side of the equation.
12 + -12 + -22x = 56 + -12

Combine like terms: 12 + -12 = 0
0 + -22x = 56 + -12
-22x = 56 + -12

Combine like terms: 56 + -12 = 44
-22x = 44

Divide each side by '-22'.
x = -2

Simplifying
x = -2

See similar equations:

| 10x-136=4x-10 | | 5x+32=9 | | 3x^2+23x-36=0 | | 2(3y-8)=5y | | 3x-9=-3x+12 | | 7x+3(3x-7)=-1-4x | | 285-3x=42x-20 | | 3x+21=171 | | 2k^2-13k-24=0 | | x^2+9x-30=6 | | 2(m+2)=5m-5 | | 20t-29=6t-11 | | 35=s(s-2) | | 8-3(5-2x)=8(x-1)-11 | | (y-4)-(y+5)=8y | | 6c+13=8c | | 3x-(4-x)=8 | | 3u^2-12u+3=0 | | 28a^2=4a | | 36x^2-9x^2= | | -(3-5(-a-3)-7)=[(5-a)-7-8] | | 5t-3(t-2)=t+6 | | 4x^2=4y^2+16 | | (9x)4x= | | 14t+8=8t+14 | | 9x-4(-2)=x+20 | | b(x)+g(y)=j | | -8*0+7y=-56 | | -3.6x-5.9=1.3 | | y=12x+1 | | 4x+5=85-4x | | bx+gy=j |

Equations solver categories